1983
DOI: 10.1002/bip.360220703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the presence of water on lysozyme conformation

Abstract: It is thought that there is little or no change in globular protein conformation upon removal of solvent water. This idea is supported by a number of ~t u d i e s~,~,~ on lysozyme which are consistent with a constant conformation as the protein is taken from aqueous solution to complete dryness. We now report a difference hydrogen-exchange study in which lyophilized lysozyme samples, either completely dry or hydrated a t a high relative humidity, were compared with lysozyme in solution. The results provide str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…Obviously, it is the possible conformational changes that are of particular interest. Although the available X-ray evidence is insufficient to prove that they do occur, recent studies on the flexibility of protein molecules (Frauenfelder, Petsko & Tsernoglou, 1979;Artymiuk, Blake, Grace, Oatley, Phillips & Sternberg, 1979;Huber, 1979;Wagner & Wuthrich, 1982;Wagner, 1983;Ribeiro, King & Jardetzky, 1983;, including that caused by hydration (Baker, Hansen, Bhaskara Rao & Bryan, 1983;Poole & Finney, 1984), suggest that conformational changes may occur in structural transformations caused by loss of water. In addition to changes in humidity, changes in ionic strength or the pH of the medium are also known to cause structural transformations in protein crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Obviously, it is the possible conformational changes that are of particular interest. Although the available X-ray evidence is insufficient to prove that they do occur, recent studies on the flexibility of protein molecules (Frauenfelder, Petsko & Tsernoglou, 1979;Artymiuk, Blake, Grace, Oatley, Phillips & Sternberg, 1979;Huber, 1979;Wagner & Wuthrich, 1982;Wagner, 1983;Ribeiro, King & Jardetzky, 1983;, including that caused by hydration (Baker, Hansen, Bhaskara Rao & Bryan, 1983;Poole & Finney, 1984), suggest that conformational changes may occur in structural transformations caused by loss of water. In addition to changes in humidity, changes in ionic strength or the pH of the medium are also known to cause structural transformations in protein crystals.…”
Section: Discussionmentioning
confidence: 99%
“…Two phases are present such that (5) A special case, equilibrium hysteresis, only has phase I present on absorption and phase I1 present on desorption.8 A convenient free energy change for describing this model is where x represents the mole fraction of phase 11. In this change the first term represents the free energy of compression as p 1 -+ p z and n increases due to reversible sorption (for which the free energy change is 0).…”
Section: Model Iv: Slow Phase Change Hysteresismentioning
confidence: 99%
“…For example, the results of Fourier-transform infrared (FTIR) spectroscopic investigations of hen egg-white lysozyme were interpreted to indicate that lysozyme structure in either aqueous solution or the lyophilized state is the same (3)(4)(5)(6). This conclusion was supported by some hydrogen isotope-exchange studies (6,7) but contradicted by others (8). Raman (9)(10)(11) and solid-state NMR (12) studies have suggested significant (reversible) structural changes occurring in lysozyme upon lyophilization.…”
mentioning
confidence: 99%